Workshop on Technical Drawing Using AutoCAD Mechanical for High School and Vocational School Teachers - Ade Supriatna; Didik Sugianto; Sarah Isniah; Gita Prawesti (JEPTIRA, 2025)
Mastery of technical drawing is an important skill in the world of education, especially in the field of engineering, including for high school teachers or equivalent who teach vocational fields such as mechanical engineering, automotive, and machining design. AutoCAD Mechanical as a Computer-Aided Design (CAD) software provides various features that facilitate the creation of technical drawings according to international standards. This community service activity aims to improve teachers' competency in creating technical drawings using AutoCAD Mechanical, so that they can integrate these skills into the learning process. The training was attended by 20 teachers from various vocational and general high schools. The implementation method included material delivery, demonstrations, and direct practice with instructor guidance. The results of the activity showed that 85% of participants were able to create 2D and 3D technical drawings according to ISO standards with an accuracy level above 90%. This training is expected to improve the quality of learning in schools, so that graduates have engineering design competencies relevant to industry needs